Isoflavones Induce BEX2-Dependent Autophagy to Prevent ATR-Induced Neurotoxicity in SH-SY5Y Cells - Peng Li; Kun Ma; Hao-Yu Wu; Yan-Ping Wu; Bai-Xiang Li (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Atrazine (ATR) is a broad-spectrum herbicide in wide use around the world. However, ATR is neurotoxic and can cause cell death in dopaminergic neurons, leading to neurodegenerative disorders. Autophagy is the basic cellular catabolic process involving the degradation of proteins and damaged organelles. Studies have shown that certain plant compounds can induce autophagy and prevent neuronal cell death. This prompted us to investigate plant compounds that might reduce the neurotoxic effects of ATR. Methods: By CCK-8 and flow cytometry, we tested the ability of five candidate compounds—isoflavones, resveratrol, quercetin, curcumin, and green tea polyphenols—to protect cells from ATR. Changes in the expression of tyrosine hydroxylase (TH) and brain-expressed X-linked 2 (BEX2), autophagy-related proteins and key factors in mTOR signaling, were detected by Western blotting. Results: Isoflavones had the strongest activity against ATR-induced neuronal apoptosis. ATR reduced the expression of TH and BEX2, whereas isoflavones increased TH and BEX2 expression. In addition, ATR inhibited autophagy, whereas isoflavones induced autophagy through the accumulation of LC3-II and decreased expression of p62; this effect was abolished by 3-methyladenine (3-MA). Furthermore, BEX2 siRNA abolished isoflavone-mediated autophagy and neuroprotection in vitro. Conclusion: Isoflavones activate BEX2-dependent autophagy, protecting against ATR-induced neuronal apoptosis.